Construction of Three-Dimensional Homogeneous NiCo2O4 Core/Shell Nanostructure as High-Performance Electrodes for Supercapacitors. Issue 12 (23rd September 2015) - Liu, Qi; Zhang, Xingming; Yang, Bin; Liu, Jingyuan; Li, Rumin; Zhang, Hongsen; Liu, Lianhe; Wang, Jun
Abstract : A novel three-dimensional homogeneous NiCo2 O4 core/shell nanowire arrays were first fabricated via a facile synthesis strategy on nickel foam as advanced binder-free electrodes. The structure and morphology of the as-synthesized samples have been characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Energy dispersive X-ray spectrometry (EDS) and transmission electron microscopy (TEM). This novel NiCo2 O4 /NiCo2 O4 core/shell nanowire arrays exhibited superior electrochemical performances, including high specific capacitance of 2041 F g −1 at current density of 5 mA cm −2, excellent rate performance with a capacitance retention of 88% as the current density increases from 5 to 50 mA cm −2 and good long-term cyclic stability. These outstanding electrochemical characteristics are mainly attributed to the superstructure, which provides a large number of electroactive sites for redox reaction, shortens the ion diffusion paths and enhances the morphological stability in the electrochemical process.